Environmental flow assessment using multiple data-driven numerical models on aquatic habitants of the Selangor River basin, Malaysia - Mohammad Haroon, Hairan (2023)
Rivers are essential ecosystems that provide freshwater and support biodiversity, but they are under threat from human activities such as pollution, channelization, abstraction, and damming. This study aims to assess the environmental flow of the Sg. Selangor River, which is necessary for the sustainability of aquatic ecosystems. The Sg. Selangor River basin in Malaysia is a crucial water resource, supplying water to over 60% of the population in the state of Selangor and the Federal Territory of Kuala Lumpur. The mean annual rainfall ranges from 2400 – 3000 mm, with a distinct wet season during the SWM (April-May) and NEM (Oct-Dec), while dry season in Jan-Mar and June-Sept. Although the basin receives abundant rainfall, drought is still a frequently occurring phenomenon. Various types of data analysis approaches and modelling techniques were adopted in this study, where both primary and longterm historical hydrological datasets were used. The water flow data analyzed covers a length of 60 years (1960 to 2020). The study utilizes hydrological and habitat simulation methods, including the Flow Duration Curve-Environmental Management Class (FDC-EMC), Indicator Hydrologic Alteration (IHA), Water Quality Index (WQI), and hydraulic-ecological simulation using PHABSIM and SEFA models. The Water Quality Index (WQI) scores for the river is 84.3 and 85.3 for normal flow and high flow condition, respectively which indicate a clean condition in the regulated system. Meanwhile, the Flow Duration Curve- Environmental Management Class (FDC-EMC) analysis of the 60 years’ historical flow data suggested Sg. Selangor River be managed under EMC class C, with min-max flow values of 3.35 - 98.09 m3/s for optimum environmental flow requirement. The IHA analysis results that the minimum amount of flow or 99.9% exceedance flow in the pre-impact period is 0.69 m3/s, while for the post-impact period is 6.16 m3/s. In addition, the results suggest that the river flow is highly regulated by the dam operation, which affects the environmental flow maintenance and may not meet the required environmental flow requirements due to the constant rate of dam release. The particle size analysis reveals that the river bed is dominated by sandy gravel and sands ranging between 0.18 to 4.00 mm, and the upper section near the dam is dominated by gravel and large sands, indicating active erosive flow. The habitat suitability criteria for Hampala macrolepidota, a native fish species, are used to define the inputs for the hydraulic-ecological simulation. The results indicated the HSC for the species’ depth preference fell within 0.7 to 1.05 m as suggested by SEFA, while an exact value of 1.14 m was suggested by PHABSIM. Likewise, the velocity preferred by the species ranged between 0.6 to 0.9 m/s or the exact value of 0.786 m/s, as suggested by SEFA and PHABSIM respectively. However, this amount differs in various sampling stations. The flows amount of 6.2 m3/s, 14.5 m3/s, 2.5 m3/s, and 3.5 m3/s are needed in stations 2 to 5, respectively. Both PHABSIM and SEFA models provide reliable estimations of environmental flow, with SEFA suggesting an interval of Environmental Flow Allocation for better management flexibility and defining acceptable objectives to all stakeholders in the Sg. Selangor River. The findings of this study could contribute to the development of sustainable river basin management plans and improve the management of water resources in the Sg. Selangor River basin.